EKSISTENSI AGAMA DALAM ERA GLOBALISASI - Ahmad Muttaqin (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2014)
This paper discusses the existence of religion in globalization era.Religious values, which are private, sacral, and transcendent, interact with theglobalization circle, which seems to be contradictory with religion.Globalization is utilitarian as its nature and it results in vanish of local values or cultures. However, none can avoid, neither can religious people. Responds to globalization frequently occur in extreme behavior since some people thinks that globalization will threat their existence in this world. Such responds make the people labeled as fundamentalists or terrorists, and many of them have religious background. Some of religious groups extremely rejecting globalization can be found states of former USSR, Japan, and Iran. Finally, this paper presents the forms and positions of religion suggested by four figures, i.e. Immanuel Wallerstein, John Meyer, Roland Robertson, and Niklas Luhmann. They suggest that the religions will keep their existence if they adopt the values of globalization and make themselves the instrument of communication as well as political and economic interaction of the world’s interaction. Religion should evolve from narrow mindedness to a broader, new, and universal values.